Shift in cropping pattern to horticulture from agriculture – A silent revolution - Vincent, A; Kumar, M Senthil (Indian Horticulture, 2020)
India is predominantly a food crop producing country in the world and a leading producer of pulses (25%), rice (22%), wheat (13%) and cotton (25%). India ranks second in production of both vegetables and fruits with the share of 12.40 and 13.30% to the world’s total production in 2013-14. Moreover, the vegetables and fruits alone accounted for 60.76 and 29.70% of total horticultural production in the country during 2011-12. In 2015-16, the area and production of food grains (rice, wheat, coarse cereals and pulses) were around 122.65 million ha and 252.22 MT respectively, as compared to 120.08 million ha and 198.36 MT in 2004-05.